2017
DOI: 10.1002/aic.15941
|View full text |Cite
|
Sign up to set email alerts
|

Automated measurements of gas‐liquid mass transfer in micropacked bed reactors

Abstract: Gas-liquid mass transfer in micropacked bed reactors is characterized with an automated platform integrated with inline Fourier transform infrared spectroscopy. This setup enables screening of a multidimensional parameter space underlying absorption with chemical reaction. Volumetric gas-liquid mass-transfer coefficients (k L a) are determined for the model reaction of CO 2 absorption in a methyl diethanolamine/water solution. Parametric studies are conducted varying gas and liquid superficial velocities, pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 36 publications
0
61
0
Order By: Relevance
“…Zhang et al proposed a two‐phase hydrodynamic model incorporated capillary pressure effect into the Holub model and the model predicted the hydrodynamic data well for four types of glass beads (150–212, 250, 300–355, 355–425 μm). The gas–liquid mass‐transfer coefficients ( k L a ) is also found in the range of 0.12~0.39 s −1 in μPBRs, which is about 1–2 orders of magnitude larger than that of large‐scale TBRs. In general, the previous research showed the small dimension of particle packing in μPBRs generates a better mass transfer rate, and at the same time causes the gas–liquid phase maldistribution and results in high pressure drop and energy consumption.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Zhang et al proposed a two‐phase hydrodynamic model incorporated capillary pressure effect into the Holub model and the model predicted the hydrodynamic data well for four types of glass beads (150–212, 250, 300–355, 355–425 μm). The gas–liquid mass‐transfer coefficients ( k L a ) is also found in the range of 0.12~0.39 s −1 in μPBRs, which is about 1–2 orders of magnitude larger than that of large‐scale TBRs. In general, the previous research showed the small dimension of particle packing in μPBRs generates a better mass transfer rate, and at the same time causes the gas–liquid phase maldistribution and results in high pressure drop and energy consumption.…”
Section: Introductionmentioning
confidence: 87%
“…The reactor was made of stainless steel with a length of 10 cm, the inner diameter of 3.87 mm, and the outer diameter of 6.35 mm (1/4 in.). More details about the reactor can be found in the literature . Each foam packing was cut into cylindrical shape by laser machine with a diameter of 3.87 mm and a height of 4 mm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elastomeric microparticles loaded with a metal catalyst (Pd) are then loaded in a tubular Teflon reactor to construct a microparticle‐packed bed reactor (μ‐PBR) (Figure ). The μ‐PBR offers an increase in catalytic surface area and improved mass transport within the continuous flow reactor for biphasic C‐C cross‐coupling reactions while maintaining the Pd‐loaded elastomer's catalytic activity and the benefits of flow processes over batch methods …”
Section: Introductionmentioning
confidence: 99%